FUNGSI INFORMASI YANG DIPERLUKAN DI INSTITUSI PENELITIAN PERTANIAN - Fawzia Sulaiman (Agro Ekonomi, 2002)
ABSTRACT:In the globalization era, the generation and development of agricultural technology will influence the competitiveness of Indonesian agricultural products in the global market. In this respect, the critic on unreadiness of Indonesian universities as research universities and the low adoption rate of technology being generated by agricultural research institutions, need a serious attention from all parties dealing with the generation and development of agricultural science and technology. The critic also implies that agricultural research institution in universities and other agricultural research institutions, especially public agricultural research institutions within the Agency for Agricultural Research and Development and the Assessment Institute for Agricultural Technology, should become credible research based agricultural technology and information. Furthermore, the science and technology being generated and developed by those research institutions will be useful if they can be accessed easily in a relatively short periode of time. This is especially true as an agricultural research needs relatively a high financial support, and it should be considered as investment to obtain the greatest beneficial outcomes and impact for the agribusiness society and regional agricultural development. For this reason, an agricultural research institution needs to have an effective information system and management to promote and disseminate its research results. This paper discusses the information function that needs to be conducted in an agricultural research institution.